FAKTOR - FAKTOR YANG MEMPENGARUHI KEBIJAKAN HUTANG PERUSAHAAN MANUFAKTUR - STEVEN STEVEN; LINA LINA (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2011)
The purposes of this study are to obtain empirical evidence and test the factors that affect the debt policy among listed companies in Indonesian Stock Exchanges. The factors are dividend policy, investment, firm growth, asset structure, size, profitability, and managerial ownerships. This study was carried out on the companies that are listed as manufacturing company in period of 2006 - 2009 at Indonesian Stock Exchange. Multiple regressions analysis is used to test the hypothesis and purposive sampling meth od used to take the samples. The conclusions of this research are dividend policy, asset structure, and profitability affect the company’s debt policy. While investments, firm growth, size, managerial ownerships have no effect to the firm’s debt policy.